Prevalence of hypodontia of permanent dentition in a sample of orthodontic patients In Erbil City: An orthopantomograph study - Mohammed, Rebin Ali; Abduljabbar, Omar Fawzi; Saleh, Muhammad Husain (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Developmentally missing teeth include hypodontia, oligodontia, and anodontia. In the case of absence of one or more teeth or supernumerary one, the need for treatment is very great. Aesthetic concerns, periodontal diseases and malocclusion are some of the complications following hypodontia. This study aimed to find out the prevalence and distribution of hypodontia in Erbil orthodontic patients in relation to the side, jaw, tooth types and gender. Methods: Orthopantomograms of 600 patients (10-34 years old), seeking orthodontic treatment from different orthodontic clinics in Erbil city between 2014 and 2015 were evaluated. A tooth diagnosed as congenitally missing when cannot be identified or discerned radiographically on the basis of calcification and there is no evidence of extraction. Results: The prevalence of hypodontia was 6.66%. Maxillary lateral incisors were most frequently missing (42.68%), followed by mandibular second premolars (19.51%). Hypodontia was more frequently found in females with no statistically significant difference. 62.5% of hypodontia located in maxilla while 27.5% located in the mandible and only 10% was in both arches in the same patient. Conclusion: The pattern and prevalence of hypodontia are different among races and ethnic groups. The prevalence of hypodontia in Erbil orthodontic patients was 6.6%. Upper lateral incisor was the most frequently missing teeth. Tooth agenesis in the upper arch was more prevalent than in the lower arch.